Artificial intelligence and digital systems engineering - Badiru, Adedeji Bodunde, 1952- (Boca Raton, FL : CRC Press, 2022)
"The resurgence of artificial intelligence has been fueled by the availability of the present generation of high-performance computational tools and techniques. This book is designed to provide introductory guidance to artificial intelligence, particularly from the perspective of digital systems engineering. Artificial Intelligence and Digital Systems Engineering provides a general introduction to the origin of AI and covers the wide application areas and software and hardware interfaces. It will prove to be instrumental in helping new users expand their knowledge horizon to the growing market of AI tools, as well as showing how AI is applicable to the development of games, simulation, and consumer products, particularly using artificial neural networks. This book is for the general reader, university students, and instructors of industrial, production, civil, mechanical, and manufacturing engineering. It will also be of interest to managers of technology, projects, business, plants, and operations"--
OCLC-licensed vendor bibliographic record.
Keywords: Systems engineering -- Data processing; Artificial intelligence; TECHNOLOGY / Manufacturing; COMPUTERS / Neural Networks